Tarte Cottage / Ahmad Nawawi Muhamad … [ et al.] - Muhamad, Ahmad Nawawi; Masri, Ahmad Safarin; Samsulbahri, Mohd Shahrizan; Zamri @ Zimri, Mohd Taufik; Mohd Diah, Tajul Fitri (2006)
Tarte Cottage is the upcoming bakery house which has a good and bright potential as well as welcoming bright future in food industry generally, pastries making specifically. As the name sounds, Tarte Cottage is specialized in offering home made and freshly oven bake of variety delightful tarts. Going beyond that, Tarte Cottage also offers unique pastries and cakes. To fulfill customer needs and demands, Tarte Cottage always welcome any requisition to supply pastry products for parties and anniversaries. Malaysia has a population of 25 million composed of three large ethnic groups; Malays, Chinese and Indians, accounting for respectively 66%, 26% and 7% of the total population. Various tribes living primarily on Borneo constitute the remaining 1%. The majority of the people reside on the west coast of the peninsular, where the capital Kuala Lumpur, Penang, Johor Bahru and Ipoh are the most attractive business areas. The concentration of the population within these areas, combined with a modern infrastructure system, facilitates market entry for companies seeking to explore business opportunities in Malaysia. The overall economic outlook for Malaysia looks very positive. After recording GDP growth rates of 5.1% in 2003 and 7.1 % in 2004, the expected rate for 2005 continue the positive development with around 5.5 % growth. This shows that the Malaysian economy is on the right track to recover from the economic downturn following the Asian crisis in 1997-1998. For new companies within the bakery and confectionery industry this is indeed very promising, as the purchasing power of the population is rising and subsequently creating an increasing demand for high-quality products. The Malaysian bakery and confectionery industry is in a period of change and expanding its precincts with the shift in consumers' preferences. In 2004 the bakery and confectionery products reached RM 2 billion, growing at 3 % in current value terms over the previous year. According to industry analysts, the growth can be attributed to the rising health awareness in Malaysia. Similar to other packaged foods, such as confectionery products, consumers are becoming more concerned with their health. Throughout 2005 the health trend is expected to continue to be the main driver of growth for bakery products, in particular within the bread segment. Recent product launches of more health-oriented products signifies the potential of value added products in Malaysia. The current development in the industry is also a consequence of the economic growth in Malaysia. The increasing purchasing power has created a more western inspired demand pattern among the Malaysian consumers, which has lead to the entry of a large number of international fast food chains and the emergence of an abundance of foreign products in the Malaysian retail sector. The Bakery and Confectionery industry is, however, still to a large extend dominated by local players offering a more traditional product assortment. This leaves a great potential for new companies to profit on the Malaysian market. To create an overview of the business opportunities for new companies in Malaysia, the following sections outline the characteristics and developments of the retail sector, the franchise sector, the hotel sector and the institutional sector.